Еstimation of Therapeutic Effect of Endonasal Electrophorosis with Methylethylpyridinol in Partial Optic Nerve Atrophy - A. M. Razumovskaya; M. I. Razumovsky; Yu. A. Koroviansky; E. S. Razumovsky (Oftalʹmologiâ)
Purpose: to evaluate the therapeutic effect of the drug Emoxypin administered by the method of endonasal electrophoresis to patients with partial atrophy of the optic nerve (PAON).Patients and methods. The treatment was conducted in 43 patients, the average age was 53 ± 2 years, with partial optic nerve  atrophy of different etiology. The main group consisted of 22  patients who received Emoxypin by endonasal electrophoresis and a  comparison group of 21 people who received Emoxypin by  parabulbar injections. Each patient underwent ophthalmological  examination, which included: visometry, perimetry, refractometry,  biomicroscopy, ophthalmoscopy, examination of visual performance,  evaluation of the state of bulbar microcirculation (general  conjunctival index — OCI). In addition, electrophysiological studies  of the vision organ carried out: the critical frequency of flicker fusion  (CSFM) and the electrical sensitivity of the eye (EF).Results. The results of statistical analysis showed the effectiveness of the drug Emoksipin for the treatment of PAON by endonasal  electrophoresis and revealed improvement in visual functions:  widening the field of view to white, red and green colors, reducing  visual fatigue, improving electrophysiological parameters and bulbar microcirculation.Conclusion. Evaluation of the effectiveness of Emoxypin use by  endonasal electrophoresis with partial optic nerve atrophy of various  etiologies showed a statistically significant positive therapeutic effect (79 %) in the form of restoration of visual functions. With parabulbar injection of this medicine, as well as with endonasal electrophoresis  in 81 %, the field of view was widened from 5° to 25° in various  meridians, the number of relative cattle in the field of vision  decreased, and in both groups, there was an improvement in visual  performance. Among patients who underwent endonasal electrophoresis, no side effects were observed.